Average Current Reconstruction Method for Ultra-Low Inductance PMSM Using a Single DC-Link Current Sensor - Gyeong-Sik Lee; Min-Seok Chae; Jun-Sik Hwang; Hyeon-Gyu Choi (IEEE Access)
This article proposes a method to minimize current reconstruction errors when driving ultra-low inductance permanent magnet synchronous motors (PMSMs) using a single current sensor system for three-phase voltage source inverters. The single current sensor system is regarded as a solution for reducing cost and size in PMSMs vector control systems. However, this approach has inherent limitations, as it introduces current reconstruction errors due to sampling timing constraints and exhibits dead zones where current reconstruction is impossible. Voltage injection methods can be used to avoid dead zones, but these methods generate additional current ripples, which further worsen current reconstruction error. In particular, in ultra-low inductance PMSMs, the low inductance characteristic intensifies current ripples, which can ultimately lead to drive failures in low-speed operating regions. To address these challenges, this paper proposes the Extended Switching Signal Split Pulse Width Modulation (EXSSS-PWM) method, which minimizes current reconstruction errors and mitigates dead zone issues without circuit configuration changes or motor parameter dependency. Experimental results demonstrate that the proposed method provides superior current reconstruction performance and is more suitable for ultra-low inductance motor systems compared to conventional methods.